2012
DOI: 10.1037/a0027344
|View full text |Cite
|
Sign up to set email alerts
|

Psychodynamic psychotherapy of ADHD: A review of the literature.

Abstract: Contributions of psychodynamic psychotherapy to the treatment of children with attention deficit hyperactivity disorder (ADHD) have been sparse. However, mixed results of other interventions, including behavior therapy and medication, call for a systematic examination of psychodynamic contributions to treatment of ADHD children. A systematic review of the literature on psychodynamic psychotherapy with ADHD children yielded a combination of 23 case studies, research reports, and theoretical writings. Questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
(147 reference statements)
0
15
0
Order By: Relevance
“…Over the years, several systematic reviews of treatments for adult ADHD have been published. Searches were undertaken through Joanna Briggs Institute Evidence Synthesis, The Cochrane Database of Systematic Reviews, and the Campbell Library show some of these reviews are specific to the efficacy of a particular intervention approach, such as psychodynamic therapy [ 35 ], homoeopathy [ 36 ], Cognitive Behavioural Therapy (CBT) [ 37 – 41 ], Mindfulness [ 42 , 43 ], and Meditation [ 44 , 45 ]. Others have been focused on efficacy [ 2 , 15 , 16 , 46 48 ], long term outcomes [ 10 , 49 ], or guidance [ 50 ].…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, several systematic reviews of treatments for adult ADHD have been published. Searches were undertaken through Joanna Briggs Institute Evidence Synthesis, The Cochrane Database of Systematic Reviews, and the Campbell Library show some of these reviews are specific to the efficacy of a particular intervention approach, such as psychodynamic therapy [ 35 ], homoeopathy [ 36 ], Cognitive Behavioural Therapy (CBT) [ 37 – 41 ], Mindfulness [ 42 , 43 ], and Meditation [ 44 , 45 ]. Others have been focused on efficacy [ 2 , 15 , 16 , 46 48 ], long term outcomes [ 10 , 49 ], or guidance [ 50 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…A group intervention [ 294 ], single [ 295 , 296 ] or double case studies [ 297 299 ] were reviewed, as well as an evaluation study [ 300 ]. Much of the literature consists of literature reviews [ 35 , 301 304 ] and guidance pieces [ 152 , 305 , 306 ], which demonstrate considerable debate in the characterisation and aetiology of ADHD. Early papers reflect issues in clinical approaches by highlighting the importance of considering ADHD diagnosis as defined by DSM-IV in light of epidemiological evidence [ 301 , 307 ].…”
Section: Results and Analysismentioning
confidence: 99%
“…Current interventions for emotional and behavioral symptoms associated with ADHD include pharmacotherapy and psychotherapy. Psychodynamic (Gilmore, 2000, 2002; Conway, 2012) and cognitive behavioral therapy (Safren et al, 2010; Antshel et al, 2011, 2012) are two types of psychotherapeutic approaches that have been utilized for ADHD and shown to be beneficial. The drawback of psychotherapy is that it is expensive, not always available, and may be challenging in the setting of ADHD in which children have difficulty in focusing.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A recent literature review of psychodynamic psychotherapy for ADHD children (Conway, 2012) reported 13 case studies, one prevention research study using pre-post-treatment design, and one retrospective outcome study of patients' charts. The Frankfurt Prevention Study, a cluster randomized controlled trial, compared children who underwent the psychoanalytically based ADHD and other disruptive disorders prevention program, Early Steps, with an untreated control group in 14 daycare centers in Frankfurt, Germany.…”
Section: Introductionmentioning
confidence: 99%